2016
DOI: 10.1002/bsl.2244
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing treatment team recommendations to review tribunals for forensic psychiatric patients

Abstract: It is the responsibility of forensic psychiatric hospitals to detain and treat patients, gradually reintegrating them into society; decisions to release patients must balance risk to the public with maintaining the least restrictive environment for patients. Little is known about the factors considered when making such decisions and whether these factors have been empirically linked to future risk of violence. The current study explores the factors predictive of forensic treatment teams' recommendations for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 31 publications
(39 reference statements)
0
31
0
Order By: Relevance
“…These will be summarized in the remainder of this section along with frequently confirmed prior findings since they have informed the primary set of variables explored in the present study (also see Table 1 for a summary). Past researchers studied patients from different security settings (25)(26)(27) or regardless of their moving (or not moving) from one level of security to another (1,15,16,28,29). In some research, factors which were found to be relevant to patients' transfer from a medium to a minimum security setting were set equal to those relevant to patients' discharge into the community, and vice versa (27).…”
Section: Findings and Inconsistencies Of Relevant Prior Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…These will be summarized in the remainder of this section along with frequently confirmed prior findings since they have informed the primary set of variables explored in the present study (also see Table 1 for a summary). Past researchers studied patients from different security settings (25)(26)(27) or regardless of their moving (or not moving) from one level of security to another (1,15,16,28,29). In some research, factors which were found to be relevant to patients' transfer from a medium to a minimum security setting were set equal to those relevant to patients' discharge into the community, and vice versa (27).…”
Section: Findings and Inconsistencies Of Relevant Prior Researchmentioning
confidence: 99%
“…There is also some evidence that emotional neglect during childhood has a prolonging effect (7). Socio-demographic variables associated with a reduction of time spent in inpatient treatment included being a parent (1), good contact with one's family or good social support (26)(27)(28), and living in a close relationship (16). While some studies reported prolonged inpatient treatment for certain religious minorities (28) and patients having migrated (7), others reported shorter length of stay for immigrants (16) and ethnic minorities (17).…”
Section: Findings and Inconsistencies Of Relevant Prior Researchmentioning
confidence: 99%
See 3 more Smart Citations